La Vie En Rose at the top? Why positive (negative) information goes up (down) in a hierarchy - du PLESSIS, Christilene (Institutional Knowledge at Singapore Management University, 2013)
Can the hierarchical relationship between a sender and a recipient of WOM information affect the type of information shared? Two studies demonstrate that senders of a WOM message tend to share significantly more positive (negative) information when addressing a recipient higher (lower) in the hierarchy, relative to negative (positive) information.